Experimental Study on the Vibration Control Effect of Long Elastic Sleeper Track in Subways - Xiaopei Cai; Dacheng Li; Yanrong Zhang; Qian Miao; Rixin Cui (Shock and Vibration)
The vibration effect of urban rail transit has gained attention from both academia and the industry sector. Long Elastic Sleeper Track (LEST) is a new structure for vibration reduction which has recently been designed and applied to Chinese subways. However, little research has been devoted to its vibration reduction effect. In this study, field tests were conducted during peak transit hours on Beijing Subway Line 15 to examine the vibration reduction effects of the common ballastless track and LEST on both straight and curved sections. The results demonstrate that although LEST increases the wheel-rail vertical forces, rail vertical displacements, and rail accelerations to some extent, these effects do not threaten subway operational safety, and vibrations of track bed and tunnel wall are positively mitigated. LEST has an obvious vibration reduction effect at frequencies above 40 Hz. In straight track, the vibration of bottom of the tunnel wall measured in one-third octave bands is reduced by 10.52 dB, while the vibration at point on the tunnel wall at 1.5 m height is reduced by 9.60 dB. For the curved track, the vibrations at those two points are reduced by 9.35 dB and 8.44 dB, respectively. This indicates that LEST reduces vibrations slightly more for the straight track than for the curved track.